Collaborative decision support for spatial planning and asset management: IIUM total spatial information system - Abdullah, Alias; Abdullah, Muhammad Faris; Shahbudin, Muhamad Nur Azraei (2004)
Although geographical information system (GIS) is being used as a tool in Malaysian development process, this is being limited to the planning and design stage of the process. There have been very few Malaysian initiatives to further the usage of GIS into the operation and post-operation phases of the development process. This paper looks at the effort by International Islamic University Malaysia (IIUM) in developing GIS-based system to assist the management of her campus.